Attitudes Toward Euthanasia Among Turkish University Students - Ulas Karaahmetoglu, Gulsen; Kutahyalioglu, Nesibe Sumeyye (SAGE Publications, 2017)
This study aims to examine perceptions and attitudes toward euthanasia among university students who are pursuing bachelor’s degrees. Although the legalization and application of euthanasia are discussed commonly by health-care professionals and partially by lawyers, the ideas of other segments of society, especially university students, are taken place very rarely. The research was conducted descriptively to determine the ideas of 1,170 students at Kastamonu University from six different departments: arts and sciences, theology, tourism, nursing, school of physical education, and sports with using a questionnaire. Findings demonstrated that 73.2% of the students do not approve euthanasia. Also, it was found that there are significant differences depending on age, gender, department of study, income level, place of living, and the loss of kinsmen. This study serves as a resource for future research to understand the effects of sociodemographic characteristics on the decision of euthanasia.
Keywords: Male; Attitude to Death; Turkey; Universities; Euthanasia; Young Adult; Surveys and Questionnaires; Humans; Female; Students; 4. Education; 3. Good health